Teorema de Euler em sala de aula - Gontijo, Helen Kássia Coelho (2014)
This work is based on the study of the polyhedrons and the Euler's Theorem, by applying strategies of teaching using the concrete material, provoking improvements in the reasoning and in the geometrical perception the Euler's Theorem. Not mentioning a bit of history of tracks already made by several mathematicians who have contributed to the study of geometry, where the ideas previously applied by them teach us and help every day. Going to the presentation of a few concepts and de nitions about polyhedrons, as well as the demonstration that exist only ve polyhedrons of Plato. We've tried to expose the demonstration of the Euler's Theorem, through two researchers, Adrien Marie Legendre and of the professor Zoroastro Azambuja Filho, considering them very interesting and easy to understand. However, in the perspective that going from the concrete one is an alternative to improve the quality of teaching, it has been selected the activity Geometry of cutting soaps , which is in an article of Ana Maria Kale , see at [10], and Geometry of straws , at [9], which are based on work experiences of the same author. Before the new technologies we have opted for the mathematical software Poly, available on http://www.peda.com/poly which allows a better visualization of polyhedrons of di cult construction. All these activities have been presented to the students of the second grade in the Secondary Education to verify the Euler's Theorem through concrete experiences, obtaining this way a useful and creative geometrical knowledge, conquering the students' participation and interest.